Attractiveness of broad-based employee stock option plans to entry-level employees. - Lim, Yi Ding. (2008)
This paper looks at factors that influence the attractiveness of broad-based employee stock options. Specifically, we are interested in the level of influence that employees perceive themselves to possess, which is influenced by the compatibility between employees’ job scope and the firm’s primary activities.